2013
DOI: 10.1242/bio.20135009
|View full text |Cite
|
Sign up to set email alerts
|

Foxc1 is required by pericytes during fetal brain angiogenesis

Abstract: SummaryBrain pericytes play a critical role in blood vessel stability and blood–brain barrier maturation. Despite this, how brain pericytes function in these different capacities is only beginning to be understood. Here we show that the forkhead transcription factor Foxc1 is expressed by brain pericytes during development and is critical for pericyte regulation of vascular development in the fetal brain. Conditional deletion of Foxc1 from pericytes and vascular smooth muscle cells leads to late-gestation cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 61 publications
(99 reference statements)
3
66
0
1
Order By: Relevance
“…Eighteen patients with either a FOXC1 mutation or copy number variation (CNV) (comprising missense sive involvement of Foxc1 in vascular development (14)(15)(16). The latter encompasses essential roles in arterial specification, angiogenesis regulation, endothelial lymphatic cell sprouting (17), as well as a requirement for Foxc1 in brain pericytes (18). Here, we demonstrate a role for FOXC1 in cerebrovascular disease through targeted genome-wide association (GWA) analysis, MRI of glaucoma patients with FOXC1-attributable Axenfeld-Rieger syndrome (ARS), and detailed zebrafish analyses.…”
Section: Mutation Of Foxc1 and Pitx2 Induces Cerebral Small-vessel DImentioning
confidence: 78%
“…Eighteen patients with either a FOXC1 mutation or copy number variation (CNV) (comprising missense sive involvement of Foxc1 in vascular development (14)(15)(16). The latter encompasses essential roles in arterial specification, angiogenesis regulation, endothelial lymphatic cell sprouting (17), as well as a requirement for Foxc1 in brain pericytes (18). Here, we demonstrate a role for FOXC1 in cerebrovascular disease through targeted genome-wide association (GWA) analysis, MRI of glaucoma patients with FOXC1-attributable Axenfeld-Rieger syndrome (ARS), and detailed zebrafish analyses.…”
Section: Mutation Of Foxc1 and Pitx2 Induces Cerebral Small-vessel DImentioning
confidence: 78%
“…Cell density was determined by averaging the number of Erg + endothelial nuclei or Zic1 + pericyte nuclei per 40× image (230 μm×230 μm) field in at least four distinct fields as previously described (Siegenthaler et al, 2013). Pericyte:endothelial cell ratio (PC:EC) was calculated by dividing the average pericyte density by the average endothelial cell density.…”
Section: Cell Density and Proliferationmentioning
confidence: 99%
“…The Pdgfrb‐Cre line (Foo et al ., 2006), where Cre recombinase expression is driven by a transgenic fragment of the gene for platelet‐derived growth factor receptor β ( Pdgfrb ), has been used extensively to specifically target mural cells, namely vascular smooth muscle cells, pericytes and hepatic stellate cells; examples are given in ref (Abraham et al ., 2008; Foo et al ., 2006; Greif et al ., 2012; Henderson et al ., 2013; Jeansson et al ., 2011; Kogata et al ., 2009; Siegenthaler et al ., 2013; Stenzel et al ., 2009; Ye et al ., 2009; You et al ., 2014). We (Stanczuk et al ., 2015) and others (Klotz et al ., 2015) recently showed that Pdgfrb‐Cre unexpectedly also targets a large proportion of embryonic lymphatic endothelial cells (LECs) in the developing mesentery (Stanczuk et al ., 2015) and the heart (Klotz et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%